Semiconductor device with reduced threshold variability having a threshold adjusting semiconductor alloy in the device active region - ZEUN ANNEKATHRIN; REICHEL CARSTEN; KRONHOLZ STEPHAN; KAMMLER THORSTEN (2014)
Generally, the subject matter disclosed herein is directed to semiconductor devices with reduced threshold variability having a threshold adjusting semiconductor material in the device active region. One illustrative semiconductor device disclosed herein includes an active region in a semiconductor layer of a semiconductor device substrate, the active region having a region length and a region width that are laterally delineated by an isolation structure. The semiconductor device further includes a threshold adjusting semiconductor alloy material layer that is positioned on the active region substantially without overlapping the isolation structure, the threshold adjusting semiconductor alloy material layer having a layer length that is less than the region length. Additionally, the disclosed semiconductor device includes a gate electrode structure that is positioned above the threshold adjusting semiconductor alloy material layer, the gate electrode structure including a high-k dielectric material and a metal-containing electrode material formed above the high-k dielectric material.